The Mismatch Thesis. Fiction and Reality in the Accumulation of Capital - Shimshon Bichler; Jonathan Nitzan (Revista de Estudios Globales. Análisis Histórico Y Cambio Social, 2023)
Political economists, both mainstream and Marxist, find it difficult to reconcile the «real» and «financial» appearances of capital. The conventional view is that «real» capital is an objective productive entity; that «finance» merely reflects this reality; and that, unfortunately, the reflection is often inaccurate, causing the two to «mismatch». This convention, we argue, is baseless if not fraudulent. First, although economists know full well that «real» capital, comprising different capital goods, cannot have a unique objective quantity – they measure this pseudo quantity anyway, arbitrarily. Second, when they realize that their arbitrary measure of «real» capital differs greatly from the corresponding magnitude of finance, they blame the deviation on invisible fluctuations in intangible capital, investor irrationality and market imperfections. And third, they insist that «real» accumulation drives «financial» accumulation, even though their own measures show that the two processes move in opposite directions!
Keywords: P; E01; E13; B14; B24; G3; G; 330; capital accumulation; finance; Marxism; measurement; Neoclassical economics; real-nominal duality; Tobin's Q